Pengembangan tes kecerdasan sosial siswa Sekolah Menengah Atas - Paul Arjanto (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
Measurement of social intelligence on high school students are not available. The study aims to generate a instrument to measure social intelligence of high school students comprehensively. Product development of instruments and manual social intelligence for high school students who revised based on judge of two experts in instrumentation and social intelligence, readability test of the 100 high school students, reliability testing and validity testing to the 956 high school students. Expert judges by using the inter-rater agreement models show a high index between variables and sub-variables until descriptors and the items. Reliability test result by using Alpha coefficient of internal consistency obtained for 0.899. The construct validity of non-verbal test shows that there are six factors and verbal test shows that there are four factors. The validation process of exploratory factor analysis showed factor loading ranges between 0.566-0.996. The norms of social intelligence tests classify into six levels.